Stylet slow-pull versus standard suction for endoscopic ultrasound-guided fine-needle aspiration of solid pancreatic lesions: a multicenter randomized trial - Saxena, Payal; El Zein, Mohamad; Stevens, Tyler; Abdelgelil, Ahmed; Besharati, Sepideh; Messallam, Ahmed; Kumbhari, Vivek; Azola, Alba; Brainard, Jennifer; Shin, Eun Ji; Lennon, Anne Marie; Canto, Marcia I.; Singh, Vikesh K.; Khashab, Mouen A. (Endoscopy, 2018)
Background and study aim Standard endoscopic ultrasound-guided fine-needle aspiration (EUS-FNA) procedures involve use of no-suction or suction aspiration techniques. A new aspiration method, the stylet slow-pull technique, involves slow withdrawal of the needle stylet to create minimum negative pressure. The aim of this study was to compare the sensitivity of EUS-FNA using stylet slow-pull or suction techniques for malignant solid pancreatic lesions using a standard 22-gauge needle.Patients and methods Consecutive patients presenting for EUS-FNA of pancreatic mass lesions were randomized to the stylet slow-pull or suction techniques using a 22-gauge needle. Both techniques were standardized for each pass until an adequate specimen was obtained, as determined by rapid on-site cytology examination. Patients were crossed over to the alternative technique after four nondiagnostic passes.Results Of 147 patients screened, 121 (mean age 64 ± 13.8 years) met inclusion criteria and were randomized to the stylet slow-pull technique (n = 61) or the suction technique (n = 60). Technical success rates were 96.7 % and 98.3 % in the slow-pull and suction groups, respectively (P > 0.99). The sensitivity for malignancy of EUS-FNA was 82 % in the slow-pull group and 69 % in the suction group (P = 0.10). The first-pass diagnostic rate (42.6 % vs. 38.3 %; P = 0.71), acquisition of core tissue (60.6 % vs. 46.7 %; P = 0.14), and the median (range) number of passes to diagnosis (2 123 vs. 1 12; P = 0.71) were similar in the slow-pull and suction groups, respectively.Conclusions The stylet slow-pull and suction techniques both offered high and comparable diagnostic sensitivity with a mean of 2 passes required for diagnosis of solid pancreatic lesions. The endosonographer may choose either technique during FNA.